2017
DOI: 10.3892/or.2017.6165
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide sulphated derivative from Aconitum�coreanum induces cell apoptosis in the human brain glioblastoma U87MG cell line via the NF-κB/Bcl-2 cell apoptotic signaling pathway

Abstract: In a previous study, our team preliminarily investigated the bioefficacy of an extracted polysaccharide from the medicinal plant Aconitum coreanum (ACP1). In the present study, we further evaluated the antitumor efficacy of an ACP1 sulphated derivative (ACP1‑s) in the human brain glioblastoma U87MG cell line. Cell viability assay and flow cytometry results demonstrated that 400, 800 and 1,600 µg/ml ACP1‑s induced cell growth inhibition and cell apoptosis. We then investigated the underlying molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…arrest in U87MG glioblastoma cells (Arcella et al, 2017). Cytotoxic triterpenoids from Antrodia camphorata (Li et al, 2020), polysaccharides from medicinal plants like Angelica sinensis (APs) (Zhand et al, 2017), Cyclocarya paliurus (CPP) (Du et al, 2020) and Aconitum coreanum (ACP1) (Sun et al, 2018) have also shown to induce apoptosis in U87MG and U251 glioblastoma cell lines. 106…”
Section: Flow Cytometry Analysis Of Etgipl1amentioning
confidence: 99%
“…arrest in U87MG glioblastoma cells (Arcella et al, 2017). Cytotoxic triterpenoids from Antrodia camphorata (Li et al, 2020), polysaccharides from medicinal plants like Angelica sinensis (APs) (Zhand et al, 2017), Cyclocarya paliurus (CPP) (Du et al, 2020) and Aconitum coreanum (ACP1) (Sun et al, 2018) have also shown to induce apoptosis in U87MG and U251 glioblastoma cell lines. 106…”
Section: Flow Cytometry Analysis Of Etgipl1amentioning
confidence: 99%